GAMBARAN VERBAL BULLYING YANG TERJADI PADA SISWA KELAS TINGGI DI SD INPRES 5/81 SAMAELO KECAMATAN BAREBBO KABUPATEN BONE - Sudarto Sudarto; Muhammad Amin; Andi Zacky Al-Zikri (STKIP Subang, 2023)
This research is a qualitative research that aims to describe the behavior of verbal bullying that often occurs in the upper grade at SD Inpres 5/81 Samaelo, Barebbo District, Bone Regency. The research subjects were the high grade students and high grade teachers at SD Inpres 5/81 Samaelo. Data collection was carried out using interviews and documentation techniques. Data analysis techniques include: data reduction, data presentation, and drawing conclusions. Results of the study: the forms of verbal bullying that often occur in high grades at SD Inpres 5/81 Samaelo, Barebbo District, Bone Regency are mocking friends with inappropriate names, mocking friends who can't do the questions given by the teacher, shouting at friends, forbidding other friends join the group, and make fun of friends.